ANALISIS PENERAPAN SEKOLAH BERBUDAYA LINGKUNGAN HIDUP DI SD MUHAMMADIYAH 4 BATU - Hilda Nur Fadillah; Arina Restian; Rissana Aprilia Rohmah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
AbstractSchools with an environmental culture are one of the Government's programs to provide understanding to the community through education in Primary and Secondary Schools. In summary, a school with an environmental culture is an educational management that is based on the awareness and understanding of the school to overcome and maintain the environment so that it is maintained. From several years ago until now, natural disasters have occurred frequently in Indonesia. For this reason, as an effort to overcome environmental damage, education or schools with an environmental culture are needed. This research aims to analyze the implementation of an environmental culture school at SD Muhammadiyah 4 Batu. With qualitative research methods, and data collection techniques through interviews, observation and documentation. The results of this research show that at Muhammadiyah 4 Batu Elementary School an environmental culture school has been implemented, but this program is not included in special subjects. In implementing learning, teachers provide understanding, introduce and familiarize students, such as carrying out class pickets every day, reducing plastic waste, not littering, sorting waste, and planting plants in every corner of the school.